2009
DOI: 10.1517/14656560903107789
|View full text |Cite
|
Sign up to set email alerts
|

Autism: an emerging ‘neuroimmune disorder’ in search of therapy

Abstract: Background: Autism spectrum disorders (ASDs) are neurodevelopmental disorders characterized by difficulties in communication and by repetitive and stereotypic behaviors, as well as by social impairment, attention, cognitive, and learning defects. ASDs present in early childhood and their prevalence has increased significantly to 1/150 children. Despite a number of theories, the actual reasons for this increase are still not clear. There is no reliable screening test, and no definite pathogenesis or curative th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 196 publications
1
44
0
4
Order By: Relevance
“…35 Some studies have postulated that the resultant ingress of enterotoxic substances into the brains of autistic patients might provoke inflammation of nervous tissue. 36 Thus, oxidative stress could result in neuronal damage and the development and progression of autism by promoting lipid and protein peroxidation, neuroinflammation, and damage to DNA and RNA. The present study, highlighting increased OSI in autistic patients, supports the above hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…35 Some studies have postulated that the resultant ingress of enterotoxic substances into the brains of autistic patients might provoke inflammation of nervous tissue. 36 Thus, oxidative stress could result in neuronal damage and the development and progression of autism by promoting lipid and protein peroxidation, neuroinflammation, and damage to DNA and RNA. The present study, highlighting increased OSI in autistic patients, supports the above hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids such as luteolin and quercetin are anti-oxidant and anti-inflammatory [9]. They also inhibit mast cell activation [10] including 12], which is increased in ASD brains [13]. We showed that luteolin can inhibit mercury-induced human mast cell activation [14].…”
mentioning
confidence: 75%
“…Çocukiardaki nörogeli §imsel hastaiiklann olu §umunda genetik, dogumsal, metabolik, çevresel ve sosyoekonomik risk etmenlerinin etkisi olmakla birlikte önemli bir kismmda neden gösterilememektedir (1,2).…”
Section: Girlçunclassified